(untitled) (Arquivos em Odontologia, 2024)
Aim: To evaluate the anatomical location of the GPF in macerated skulls by means of linear measurements and anatomical structures, in turn providing information that can aid dentists when performing anesthetic and surgical techniques. Methods: An experimental ex vivo study was performed. The sample consisted of 55 dry skulls. Measurements were taken on the topography of the GPF: a) distance from the GPF to the median palatine suture (MPS); b) distance from the GPF to the posterior nasal spine (PNS); c) distance from the GPF to the center of the incisive foramen (IF); d) distance from the GPF to the alveolar ridge (AR); and e) distance between the right and left GPFs. The Mann-Whitney and Pearson’s Chi-Square tests were performed (α = 5%). Results: It was noted that the distance between the left and right GPFs, from the GPF to the PNS and to the IF were greater in female skulls (p < 0.05). In addition, it was possible to verify that the distances from the left and right GPFs to the AR and to the PNS were greater in male skulls. In relation to molars, no association was found between gender and the location of the GPF. Conclusion: Using varied anatomical structures, differences were found in the location of the GPF in both female and male skulls.